Smart antenna design alimented by a 4x4 butler matrix - S. Almorabeti; H. Terchoune; M. Rifi; H. Tizyi; S. Smihily (Universitas Ahmad Dahlan, 2021)
In the last decades, the development of efficient antennas for wireless power transfer applications has gained great attention from researchers worldwide and has become a vital research topic. In this paper, we propose the optimum design and implementation in microstrip technology of a switched beam smart antenna alimented by a 4x4 butler matrix (BM) for a microwave wireless power transmission system (MPT) at 5.8 GHz. The proposed smart antenna consists of a four linear microstrip patch antenna array and a 4x4 butler matrix beamforming network. It was able to form and steer four orthogonal beams in the four directions (±39°, and ±15°). Furthermore, it exhibited a high gain of 17.98 dB and good simulated and measured return losses. The design, optimization and simulation of the smart antenna components were performed using advanced design system (ADS).